Pedogenesis of pelitic rocks of the Serra da Saudade Formation - Bambuí Group - Luiz Aníbal da Silva Filho; João Carlos Ker; Danilo de Lima Camêlo; Maurício Paulo Ferreira Fontes; Marcelo Metri Corrêa; David Lukas de Arruda Silva (Revista Brasileira de Ciência do Solo, 2024)
ABSTRACT Serra da Saudade Formation corresponds to the upper part of the stratigraphic column of the Bambuí Group. Few studies have addressed the soil properties and pedogenesis of the pelitic rocks rich in potassium minerals of this formation. This study analyzed siltstone-derived soils, some of which are glauconitic (green siltstone; “verdete”), to understand the role of the main pedogenetic factors and processes in the landscape of the Central-West region of the Minas Gerais State, covered by Cerrado vegetation. Nine soil profiles were described, and their morphological, physical, chemical and mineralogical properties were analyzed. Soils were classified as Neossolos Litólicos (P1, P3, P6, P8 and P9), Cambissolos Háplicos (P2 and P5), Argissolo Vermelho-Amarelo (P4) and Argissolo Acinzentado (P7). The main active pedogenetic processes identified in the study area are melanization, goethization, argiluviation and elutriation. These are essentially controlled by the nature of the parent material and position of the soil in the relief. Soils are typically shallow, dystrophic, highly Al-saturated and contain essentially quartz and micas in the coarse fractions (sand and silt) and illite/glauconite and kaolinite in the clay fraction. In soil environments with siltstone and green siltstone under “dry forests”, the soil water pH was higher and high levels of exchangeable calcium and magnesium, a eutrophic character and high-activity clay were observed. Barium, chromium, lead and zinc contents were high in all studied soils. Green siltstone-derived soils have peculiar physical and chemical properties, divergent from those developed from other glauconitic rocks on the Earth surface. However, greenish tones in horizons are common in all these soils.